A natural bacterial strain Bacillus pumilus 16: Identification and antibiotic resistance evaluation - Alena N. Irkitova; Angelina V Malkova; Dina E. Dudnik (Acta Biologica Sibirica, 2021)
Microbial biopreparations are actively used to prevent, diagnose, and treat infectious, allergic, tumor, and autoimmune diseases in humans and animals; to stimulate the growth and development of plant crops. Natural bacterial strains with valuable technical properties are a vital biological resource for developing new biopreparations and rotating already known microbial preparations in the world market. This study describes a new natural strain B. pumilus 16, which was isolated from the rhizosphere of Cichorium. The strain was identified using morphological and physiological parameters, biochemical tests, and primers Pum-f. and Pum-r. Antibiotic sensitivity and antagonistic activity against Escherichia coli were determined by diffusion of discs and delayed antagonism methods, respectively. The new natural strain (like type strains) fermented arabinose, cellobiose, mannitol, mannose, salicin, sucrose, and trehalose, and gave a positive reaction to arginine dihydrolase, ONPG, Voges-Proskauer test. It also gave a negative reaction to inositol, raffinose, sorbitol, methyl-D-glucoside, inulin, and lecithinase. B. pumilus 16, unlike the test strains, was capable of fermenting citrate. Strain B. pumilus 16 was highly sensitive to cephalexin (37.9±0.7 mm) and enrofloxacin (25.7±8.9 mm); sensitive to ole-andomycin (17.1±1.9 mm), benzylpenicillin (18.5±1.2 mm), and monomycin (16.0±0.6 mm); resist-ant to oxacillin. By the agar blocks method (7.3±1.5 mm), a more pronounced antagonism of the new strain against E. coli was recorded than by the method of agar wells (5.3±0.6 mm). Due to the level of antagonistic activity, B. pumilus 16 was more effective than the type strains (two of which did not show an antagonistic effect). On the basis of this, the new strain can be recommended for inclusion in the bacterial preparation composition for the national economy.